Landasan Pengembangan Strategi Pembelajaran - Delia Masmuda delia; Bella wahyuni bella; Sukatin sukatin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In the learning process, strategy is a determining factor in the success of learning. With the strategy, it is hoped that learning can achieve optimal results in accordance with what is aspired to. Based on data analysis, it is concluded that the learning strategy can be said to have not been implemented properly. This can be seen from the absence of strategies used by teachers in learning, and there are still factors that are less supportive such as incomplete facilities, a less supportive school environment, and lack of student interest. To create a superior learning process/quality, it is necessary to develop special strategies that make students motivated to learn and always feel pleasure in learning. In developing these learning strategies, students become the center of attention. The criteria that must be met in a learning model or learning development are: 1) have a goal; 2) alignment with the goal; 3) systematic; 4) hold evaluation activities; and 5) fun. Therefore, the learning system can be likened to a production process consisting of input-process-output parts, which are mutually integrated. So the problem is that the work works well. The ability to develop techniques in learning because all teachers want the results of education to go well. Moreover, he is not dealing with inanimate objects, but human children who grow and develop.